Note-Taking Pairs Strategy Towards Students’ Critical Thinking Ability In Reading Comprehension - Permana, Dira; Suadiyatno, Taufik; Harmawati, Siti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
This study aimed to seek the effect of the Note-Taking Pairs strategy on the students' critical thinking skill in reading comprehension. This study used an experimental method with pre-test and post-test design. The research sample covered class XI-IPA2 which was used as an experimental group and consisted of 26 students and class XI-IPA1 was used as a control group consisting of 26 students. The instruments used in collecting data were reading test in the form of multiple-choice and observation sheets of critical thinking skills. The finding data were subsequently analyzed by using SPSS 18. The t-test results showed that the t-test value (1.754) was higher than the t-table (1.671) at the significance level 0.05. Therefore, based on these results, it can be concluded that there is a positive effect from the use of the Note-Taking Pairs strategy on the students' critical thinking skill in reading comprehension at the eleventh-grade students of SMAN 2 Narmada.